Modeling Summer Circulation and Distribution of Temperature and Salinity in the Bellingshausen Sea and on the Antarctic Peninsula Shelf - V. Maderich; K. Terletska; I. Brovchenko; A. Bezhenar (Ukrainian Antarctic Journal, 2018)
The objective of the study is to simulate the summer circulation and the distribution of temperature and salinity in the Bellingshausen Sea and on the shelf of the Antarctic Peninsula. Numerical methods are used for simulation by means the SCHISM model with an unstructured triangular horizontal grid and a vertical local sigma coordinate system (LSC2). The k-kl model of turbulence was used to  describe turbulence. Heat, momentum and salt fluxes were set on the ocean surface, which were calculated according to the ERA-Interim reanalysis. At open boundaries, the vertical distribution of temperature and salinity was determined according to the HYCOM reanalysis calculations. On the western open border, the level deviations and the vertical velocity distribution calculated by HYCOM were also specified. At the open eastern boundary of the computational domain, the radiation conditions were specified. The results of the HYCOM reanalysis were also used as initial conditions. The results of modelling the current, temperature, and salinity fields in the period February—March 2014 were compared with the available observational data on the shelf of the Antarctic Peninsula, including data from the Ukrainian Antarctic expedition. The calculated vertical distributions of temperature and salinity on the shelf are consistent with observations, in particular, in the position and magnitude of the minimum temperature of the cold intermediate layer and its temperature in the region of the Argentine Islands. Calculations have shown that the main component of the circulation is the Antarctic Circumpolar Current (ACC), which carries water to the east. In ACC, several jets are formed flowing into the Drake Strait, whereas a chain of vortices separates the shelf zone of the Antarctic Peninsula and the ACC. In the summer, a current directed southwards along the edge of the shelf, caused mainly by large-scale ocean circulation and the wind field. It was concluded that the formation of zones of upwelling and downwelling on the shelf of the Antarctic Peninsula substantially depends on the changes in the atmospheric circulation over the Bellingshausen Sea.